Assessing the threat of the polyphagous shot hole borer beetle (PSHB, Euwallacea fornicatus) and its symbiotic fungus (Fusarium euwallaceae) to deciduous fruit trees in the Western Cape Province of South Africa - Engelbrecht, Karyn (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScConsEcol)--Stellenbosch University, 2025.